The Influence of Basic Accounting Knowledge and Computer Operation Skills on Accounting Software Proficiency - Sinaga, Era Elfrida; Gaol, Vebry M. Lumban; Samosir, Hendrik E.S (Golden Ratio of Data in Summary, 2025)
This study aims to determine the effect of basic accounting understanding and computer operation on the accounting computer skills of Faculty of Economics and Business students majoring in accounting at Universitas HKBP Nommensen in 2023. Accounting computer skills are one of the important competencies that accounting graduates must have to compete in the technology-based workforce. This type of research employs a quantitative approach with an associative design. Data was collected through questionnaires and analyzed using SPSS software version 25. The sample was selected purposively from students who had taken basic accounting and accounting computer courses. The findings revealed that understanding basic accounting had no substantial impact on accounting computer skills, whereas computer operation did. Both greatly affect accounting computer abilities, with a combined contribution of 58.2%. These findings support the need to improve technical competencies in the accounting education curriculum.